Implementasi Program Integrated Participatory Development and Management of Irrigation Project (IPDMIP) Dalam Kenaikan Produktivitas Usahatani Padi Di Kabupaten Pesawaran - Yuli HS; Dewangga Nikmatullah; Sumaryo Gitosaputro (Jayapangus Press, 2023)
The research have a mean to finding an implement and achievement, active role of farmers and the role of field assistants related to the IPDMIP kegiatan which caryying by analyzing the influence of the active role of farmers, field assistants, as well as kegiatan implementation in achieving it. This research is to implement by carrying in the Way Khilau and Way Mada Irrigation Areas in Way Khilau District, Pesawaran Regency which was carried out in April 2022. The adjustment for location of this research with sampling, namely purposive sampling involving 91 farmers as respondents. The analysis itself applies the Path Analysis. Result of this research is if the implementation of the IPDMIP kegiatan is in the low category, the achievement of the kegiatan can still be said to be quite successful, and the active role of the respondents in this case the farmers involved in the IPDMIP kegiatan are iincluding in high class with field assistants who are included in in the high category for the role as a provider of education and innovation, role as a facilitation provider and executor of supervision in medium class and mediation implementer which is included in the low classification. The active role, the role of field assistants as well as kegiatan implementation have had an influence on the achievement of the IPDMIP kegiatan in Way Khilau District, Pesawaran Regency.